Systems biology approaches to enhance our understanding of drug hypersensitivity reactions. Issue 12 (December 2014) - Perkins, J. R.; Barrionuevo, E.; Ranea, J. A.; Blanca, M.; Cornejo‐Garcia, J. A.
Summary Hypersensitivity drug reactions (HDRs) encompass a wide spectrum of unpredictable clinical entities. They represent an important health problem, affecting people of all ages, and lead to a large strain on the public health system. Here, we summarize experiments that use high‐throughput genomics technologies to investigate HDRs. We also introduce the field of systems biology as a relatively recent discipline concerned with the integration and analysis of high‐throughput data sets such as DNA microarrays and next‐generation sequencing data. We describe previous studies that have applied systems biology techniques to related fields such as allergy and asthma. Finally, we present a number of potential applications of systems biology to the study of HDRs, in order to make the reader aware of the types of analyses that can be performed and the insights that can be gained through their application.